Ø§Ù„Ø¥Ø´ÙƒØ§Ù„ÙŠØ§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© ÙÙŠ Ø£Ù„ÙØ§Ø¸ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… (Ø¯Ø±Ø§Ø³Ø© Ø¯Ù„Ø§Ù„ÙŠØ©) - mufidah, nur rohmatul (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2020)
In fact, the Al-Qur'an sentence, although in accordance with the rules of Arabic grammar, there are differences the over rules, because the Al-Qur'an sentence contains information that is charming, detail and beautiful. Then, the different setting of sentences has the purpose and aim with the rules of Arabic. The sentence has a holy meaning and includes the Rabbani secret is a new sentence arrangement that has never been known in Arabic. And some Muslims collapse the rules between Arabic and Qur’an language, and what is different from understanding Arabic is considered a mistake, sometimes some Muslims misunderstand that in the arrangement of the Qur’an sentence there are language problems. From the information above, the author tries to explain some of the secrets and hidden wisdom behind this problem. Based on this background, researchers tried to examine the problem of language in the Qur'an which was discussed with semantic studies. To obtain scientific data, researchers used the literatures method with primary data sources in the form of several literatures and books such as the interpretation of Al-Zamakhsyari or Al-Alusi. Secondary data is data that supports primary data. The data of this study were obtained by descriptive method, namely collecting and analyzing related data sources which were followed up with analytical methods by analyzing data, examined through a semantic approach, namely the meaning of the language approach. The results of this discussion discuss four aspects of the problem in the Qur'an, namely the uncontinuity between ma'thuf and ma'thuf alaihi, between ifrod, tasniyah, and jama ', between na'at and man'ut, and ta'nis al-mudzakkar and tadzkir al-muannas, these problems basically do not violate the rules of language or Arabic grammar, and the Ulama 'Qur'an has explained in detail the wisdom of the structure of the text, and precisely because of the characteristics of the I'jaz the Qur'an can not only be understood from the grammatical aspect.Keywords: Language Problems, Grammar, Semantic Studies.